PREVALENCE AND ANALYSIS OF FACTORS ASSOCIATED WITH CANINE IMPACTION IN CLASS III MALOCCLUSION. - A RETROSPECTIVE CASE STUDY - G., Nithya Karpagam; Ramanathan, Visalakshi (International Journal of Psychosocial Rehabilitation, 2020)
Impacted teeth are those with a delayed eruption time or that are not expected to erupt completely based on clinical and radiographic assessment. After the third molars, the maxillary canine is the second most frequently impacted tooth in the dental arch. The prevalence of impacted maxillary canine is 0.9 to 2.2%. Knowledge of occlusion of each patient can contribute significantly to complete care and instruction. The aim of the study was to analyze the association of canine impaction to age, gender and types in class III malocclusions. This was a single retrospective study set in a university dental hospital with predominantly south Indian population. The data was collected from the electronic database of the university. A total of 50 patients were included in the study. Data tabulation was done in EXCEL then it was imported and assessed using Statistical Package for Social Science 20(SPSS, IBM corporation). A test for frequency of incidence of impacted canine among patients diagnosed with class III malocclusions was conducted. Chi-square test was conducted for association of age, gender, type of class III malocclusion. The results were descriptively presented in the form of graphs and tables. Only patients with true class III malocclusion in the age range of 13-30 yrs. were included in the study. Among the study population 78% of the patients were diagnosed with a skeletal class III and 22% of the patients were diagnosed with a dental class III. Out of the whole study population only four patients had impacted canines that is 8% of the total study population. Of the total study population, 6% of the patients with impacted canines were male and 2% of the patients were female. Canine impaction has statistically significant association to both adult and child age groups, p=0.028. Also males patients with class III malocclusions showed a higher association to canine impaction, p=0.004. Among the study population , canine impaction showed more association with dental class III patients ,( p = 0.038 ).